17-Year-Old Boy with Renal Failure and the Highest Reported Creatinine in Pediatric Literature - Vimal Master Sankar Raj; Jessica Garcia; Roberto Gordillo (Case Reports in Pediatrics)
The prevalence of chronic kidney disease (CKD) is on the rise and constitutes a major health burden across the world. Clinical presentations in early CKD are usually subtle. Awareness of the risk factors for CKD is important for early diagnosis and treatment to slow the progression of disease. We present a case report of a 17-year-old African American male who presented in a life threatening hypertensive emergency with renal failure and the highest reported serum creatinine in a pediatric patient. A brief discussion on CKD criteria, complications, and potential red flags for screening strategies is provided.